1998
DOI: 10.1007/s002709900205
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pelvic Venous Spur (May–Thurner Syndrome) with Self-Expanding Metallic Endoprostheses

Abstract: The percutaneous transfemoral placement of self-expanding metallic stents is an effective minimally invasive alternative to surgery in the treatment of symptomatic pelvic venous spur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 11 publications
1
49
0
4
Order By: Relevance
“…Contrast venography has widely been considered the gold standard diagnostic modality for MTS and has been utilized to confirm a diagnosis of MTS in several studies [5,6,12,24] . The procedure demonstrates the degree of iliac vein stenosis and can visualize any pelvic venous collaterals.…”
Section: Contrast Venography/hemodynamic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast venography has widely been considered the gold standard diagnostic modality for MTS and has been utilized to confirm a diagnosis of MTS in several studies [5,6,12,24] . The procedure demonstrates the degree of iliac vein stenosis and can visualize any pelvic venous collaterals.…”
Section: Contrast Venography/hemodynamic Studiesmentioning
confidence: 99%
“…Currently, the use of endovascular techniques in the treatment of MTS patients is considerably successful and carries less risk than invasive surgical treatments [8] . Common endovascular treatment options include catheter-directed thrombolysis, angioplasty, and ultimately stent placement [3,5,6,10,24] . Angioplasty has been found to be associated with low long-term patency rates, which indicates that the iliac vein compression may not be alleviated with solely the use of balloon angioplasty [30] .…”
Section: Treatment Optionsmentioning
confidence: 99%
“…28) Study series featuring iliac vein stenting in MTS patients have increased in number over the past decade and have generally advocated the use of endovascular techniques. 5,6,29) Recently, a retrospective review by Titus, et al identifi ed MTS patients treated via endovenous stenting and showed that the primary patency rates were 88%, 78%, and 78%, respectively, at 6, 12, and 24 months postoperatively. 30) O'Sullivan, et al reported that the overall patency rate at 1 year was 79%.…”
Section: Discussionmentioning
confidence: 99%
“…Taheri et al [6]argue that progressive symptoms will continue to develop in these patients, so the anatomic anomaly should be corrected as soon as it is identified. For this reason, surgical decompression [3, 6, 10]and more recently transluminal stenting have been recommended [12, 13, 14]. We started anticoagulant therapy and inserted a vena cava filter because our patient presented with pulmonary emboli, and anticoagulants alone were thought to be inadequate for treating his condition [12].…”
Section: Discussionmentioning
confidence: 99%